Pengembangan Media Pembelajaran Interaktif Berbasis Teknik Dasar Bola Basket untuk Meningkatkan Partisipasi Aktif Siswa - Sahabuddin; Hikmad Hakim; Muhammad Ishak; Arman Fadillah (PT. Penerbit Tiga Mutiara, 2025)
This study aims to develop an interactive learning medium based on fundamental basketball techniques and to evaluate its effectiveness in enhancing students' active participation in physical education at the junior high school level. The research employed a Research and Development (R&D) approach, modifying the Borg and Gall model into nine systematic development stages, including needs analysis, design, validation, and field testing. The research subjects consisted of 30 seventh-grade students for the limited trial and 60 students for the field trial. Validation by subject matter and media experts yielded an average score of 87%, indicating that the media is highly feasible. The limited trial results showed increased student participation across three learning domains: affective (72%), cognitive (68%), and psychomotor (70%). The subsequent field trial confirmed these findings, with an average active participation score of 81%, categorized as excellent. Additionally, quantitative data from questionnaires indicated positive responses from both students and teachers, with an average score of 85%, while qualitative data from observations and interviews revealed that the media significantly improved student motivation, engagement, and conceptual understanding. The results conclude that the developed interactive learning media is content-valid, practical for implementation, and effective in enhancing students’ active participation. These findings offer empirical contributions to the development of innovative, contextual, and applicable learning media in physical education and support the reinforcement of active participation-based pedagogy at the basic education level.